Institutional opportunities for the development of option programs for top management remuneration in the Russian Federation - I. I. Ordinartsev (Управленческие науки, 2022)
In the context of the sanctions pressure on the economy of the Russian Federation and the opportunistic behavior of certain foreign members of the boards of directors, it is necessary to develop a national model of corporate governance in terms of remuneration of top management, the level of which in Russian corporations is currently focused on the practice of foreign companies, which entails significant overpayments and causes public complaints. Companies do not personalize the payments made, do not disclose the remuneration structure as a whole, nor do the criteria by which the amounts are determined, which are the overall performance of the company, generally, techno-economic. In the world practice, of remuneration of top managers there is a shift from direct cash payments to optional programs. In Russian practice, such programs are not sufficiently developed: there is a brief information about their use, but without explaining the details. The purpose of the article is to identify institutional opportunities for the development of options for the remuneration of managers of Russian companies, and its tasks — analysis of experience of application and possibilities of development of optional programs of remuneration of the top management of Russian companies, analysis of the legislative base for allocation of its shares. In the article applied methods of generalization, analysis and synthesis in the part of the study of methodical and legislative approaches to the identification of variants for the application of option programs. There has been shown that remuneration of stocks of top management in the Russian practice is possible through shareholder agreements.